Comparative analysis of essential oil composition of Iranian and Indian Nigella sativa L. extracted using supercritical fluid extraction and solvent extraction - Ghahramanloo KH; Kamalidehghan B; Akbari Javar H; Teguh Widodo R; Majidzadeh K; Noordin MI (Dove Medical Press, 2017)
Kourosh Hasanzadeh Ghahramanloo,1 Behnam Kamalidehghan,2 Hamid Akbari Javar,3 Riyanto Teguh Widodo,1 Keivan Majidzadeh,4 Mohamed Ibrahim Noordin1 1Department of Pharmacy, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 2Medical Genetics Department, National Institute of Genetic Engineering and Biotechnology (NIGEB), 3Department of Pharmaceutics, Faculty of Pharmacy, Tehran University of Medical Sciences (TUMS), 4Breast Cancer Research Center (BCRC) Academic Center for Education, Culture and Research, Tehran, Iran Abstract: The objective of this study was to compare the oil extraction yield and essential oil composition of Indian and Iranian Nigella sativa L. extracted by using Supercritical Fluid Extraction (SFE) and solvent extraction methods. In this study, a gas chromatography equipped with a mass spectrophotometer detector was employed for qualitative analysis of the essential oil composition of Indian and Iranian N. sativa L. The results indicated that the main fatty acid composition identified in the essential oils extracted by using SFE and solvent extraction were linoleic acid (22.4%–61.85%) and oleic acid (1.64%–18.97%). Thymoquinone (0.72%–21.03%) was found to be the major volatile compound in the extracted N. sativa oil. It was observed that the oil extraction efficiency obtained from SFE was significantly (P<0.05) higher than that achieved by the solvent extraction technique. The present study showed that SFE can be used as a more efficient technique for extraction of N. Sativa L. essential oil, which is composed of higher linoleic acid and thymoquinone contents compared to the essential oil obtained by the solvent extraction technique. Keywords: Nigella sativa L., essential oil extraction, supercritical fluid extraction, solvent extraction, fatty acid composition, thymoquinone, linoleic acid